Local Wisdom in Mepum Sadimop Fairy Tale of Ketengban Tribe, Pegunungan Bintang Regency, Papua - Meku, Andir; Harjito, Harjito; Umaya, Nazla Maharani (CV. Publikasi Indonesia, 2025)
Local wisdom represents unique knowledge and practices held by specific communities, passed down through generations. This study explores the local wisdom in the Mepum Sadimop fairy tale of the Ketengban Tribe in Pegunungan Bintang Regency, Papua. Using a qualitative phenomenological approach, this descriptive research employs interviews, data grouping, and translation to analyze cultural phenomena. Findings reveal that the Mepum Sadimop fairy tale encapsulates local knowledge (e.g., tools, materials, and natural resources), cultural values (e.g., kinship, cooperation, and honesty), and traditional practices (e.g., stone-burning ceremonies and the use of Balapu attire). These elements embody the tribe's identity, social norms, and survival strategies. This study not only preserves the oral tradition but also underscores its relevance in promoting cultural education and sustainable community development. By documenting these traditions, this research contributes to safeguarding intangible cultural heritage and inspires further interdisciplinary studies on indigenous knowledge system.